ANALISIS GAYA BAHASA BERDASARKAN LANGSUNG TIDAKNYA MAKNA PADA KUMPULAN CERPEN KARYA MARIYADI - Agustina, Fitria; Priyadi, Antonius Totok; Abdussamad, Abdussamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPublic problem in this research is the direct to be based language-Style its not meaning in Collecting Short story Pak Tungkor: Mariyadi Work: Sruktural's Studying. public Problem mentioned to be limited become style of language in collecting of short story Pak Tungkor Mariyadi Work that consist on the types of language style in collecting of short story. The Method that to be used in this research is descriptive method, form qualitative research, and structural approach. data Source in this research is short story collecting text Pak Tungkor Mariyadi's Work. the data collection Technique that be done in this research is study technique dokumenter. The To be based of data analysiical-result that had be done style type retoris to Collecting of short story Pak TungkorMariyadi's Work got seven styles language that is: Aliterasimany 105, Asonansimany 48, Asindentonmany 8, Ellipseistmany 1, Eufemismusmany 12, Perifrasismany 17, and Hiperbolamany 5. This research Result to be expected can useful for reader specially teacher and student SMP. Research Hsil this to be expected also useful for student university in collecting of short story Pak Tungkor Mariyadi Work this can be made as reference to research next that related about the direct to be based language-style its not meaning. Â Keywords: Type, Language Style, and Structural